Tension, War, Peace, and Unification: South Korea’s Unification Policies in the Light of Theological-Ethical Theories of War and Peace - Lee, Chang-Ho (International journal of public theology, 2023)
This article analyzes South Korea’s unification policies and makes ethical suggestions in light of Christian theological and ethical theories of war and peace. Since 1948, South and North Korea have repeatedly confronted each other with heavily armed forces. Unification would be considered the achievement of the Korean people’s endeavour to deter military warfare and promote peace between the two Koreas. In this regard, it is understandable that unification policy-making should retain tension reduction and peaceful coexistence as its fundamental goals. Public discussions in unification policy-making inevitably involve such issues as prohibition or justification of the use of violence or military force and procedures and methods of promoting peace. In analyzing unification policies in Christian ethical terms, such Christian war-peace tenets as pacifism, just war, and holy war contribute to this analysis, given that their primary concerns lie in maintaining peace and justifying violence for the sake of peace.